Complement-Activating Capacity of Autoantibodies Correlates With Disease Activity in Bullous Pemphigoid Patients - Chiorean, Roxana M.; Baican, Adrian; Mustafa, Mayson B.; Lischka, Annette; Leucuta, Daniel-Corneliu; Feldrihan, Vasile; Hertl, Michael; Sitaru, Cassian (Frontiers in Immunology, 2018)
Background: Bullous pemphigoid is a subepidermal blistering skin disease, associated with autoantibodies to hemidesmosomal proteins, complement activation at the dermal-epidermal junction and dermal granulocyte infiltration. Clinical and experimental laboratory findings support conflicting hypotheses regarding the role of complement activation for the skin blistering induced by pemphigoid autoantibodies. In-depth studies on the pathogenic relevance of autoimmune complement activation in patients are largely lacking. Therefore, the aim of this study was to investigate the pathogenic relevance of complement activation in patients with bullous pemphigoid. Complement activation by autoantibodies in vivo as measured by the intensity of complement C3 deposits in the patients' skin and ex vivo by the complement-fixation assay in serum was correlated with the clinical disease activity, evaluated by Autoimmune Bullous Skin Disorder Intensity Score (ABSIS) and Bullous Pemphigoid Disease Area Index (BPDAI), as well as with further immunopathological findings in patients with bullous pemphigoid. Results: Complement-activation capacity of autoantibodies ex vivo, but not deposition of complement in the perilesional skin of patients, correlates with the extent of skin disease (measured by ABSIS and BPDAI) and with levels of autoantibodies. Conclusions: Our study provides for the first time evidence in patients for a pathogenic role of complement activation in bullous pemphigoid and should greatly facilitate the development of novel diagnostic tools and of more specific therapies for complement-dependent autoimmune injury. Keywords: bullous pemphigoid, complement-activating capacity of autoantibodies, complement-binding test, disease activity, ABSIS, BPDAI.